Aktywność posłów do Parlamentu Europejskiego IX kadencji na portalu społecznościowym Facebook – analiza porównawcza - Dominik Boratyn (Nowa Polityka Wschodnia, 2020)
Social media has changed the social lives of humans. The real-world activities are conducted more often on the Internet; the content posted on such social networking sites as Facebook may serve here as an example. Activity in social media is particularly important for politicians and public figures since such a means of communication allows them to maintain direct contact with voters and citizens. Social media also serves as a platform for creating an image and a personal brand of a politician. Due to the activity on these types of platforms, lesser known people can gain wider recognition and reach a larger group of recipients. However, it should be also noted that as far as public figures are concerned, increased activity does not always denote the achievement of a goal. Politics are simply unpredictable and there are many factors influencing voting preferences.